Molecular epidemiology of ESBL-producing Klebsiella pneumoniae isolates in intensive care units of a tertiary care hospital, North of Iran - Ghaffarian, Fatemeh; Hedayati, Mojtaba; Sedigh Ebrahim-Saraie, Hadi; Atrkar Roushan, Zahra; Mojtahedi, Ali (Cellular and Molecular Biology, 2018)
The emergence of extended-spectrum beta-lactamases (ESBL) producing strains become a great concern, because few antimicrobial agents remain active against them. Due to the lack of data on the genotyping characteristics and antibiotics resistance of clinical isolates of Klebsiella pneumoniae in the north of Iran, this study aimed to determine the occurrence of ESBL-producing isolates and their molecular characteristics in order to analyses their epidemiological relationships. This cross-sectional study performed on 60 K. pneumoniae isolates which were recovered from different clinical specimens within May and November 2016. Isolates were identified by standard microbiologic tests and confirmed by API 20E strip. Antimicrobial susceptibility testing was carried out by disk diffusion method. The genetic relatedness among the isolates was assessed by RAPD-PCR. Totally, the lowest level of susceptibility was toward amoxicillin/clavulanat, and nalidixic acid. On the other hand, the highest level of susceptibility was toward imipenem (86.7%). The rate of ESBL-producing isolates was 45% (27/60). There was a significant association between production of ESBLs and higher antibiotic resistance in tested isolates. The RAPD-PCR dendrogram revealed 5 major clusters with a similarity of 80% which indicates the high relatedness of the studied isolates. Twenty-one isolates out of the 27 ESBL-producing isolates were clustered in cluster A. In summary, results showed the high prevalence of multiple-drug resistant and ESBL-producing K. pneumoniae isolates in our ICUs. Also, results revealed a significant similarity between ESBL-producing isolates that necessitate restricted infection control policies and rational prescription and use of antibiotics.